Precipitation hardening in the Cu-11 wt.%Al-10 wt.%Mn alloy with Ag addition - Silva, R. A.G.; Paganotti, A.; Adorno, A. T. [UNESP]; Santos, C. M.A. [UNESP]; Carvalho, T. M. [UNESP] (Elsevier, 2015)
In this work the precipitation hardening in the Cu-11 wt.%Al-10 wt.%Mn alloy with Ag addition was studied using different experimental techniques. The results indicated that the hardening on ageing of the Cu-11 wt.%Al-10 wt.%Mn alloy is only due to bainite precipitation, while in the Cu-11 wt.%Al-10 wt.%Mn-3%Ag alloy three reactions in sequence can occur, including the bainite precipitation.
Keywords: Metals and alloys; Phase transitions